High‐density genome‐wide association mapping implicates an F‐box encoding gene in Medicago truncatula resistance to Aphanomyces euteiches. Issue 4 (28th November 2013) - Bonhomme, Maxime; André, Olivier; Badis, Yacine; Ronfort, Joëlle; Burgarella, Concetta; Chantret, Nathalie; Prosperi, Jean‐Marie; Briskine, Roman; Mudge, Joann; Debéllé, Frédéric; Navier, Hélène; Miteul, Henri; et al.
Summary: The use of quantitative disease resistance (QDR) is a promising strategy for promoting durable resistance to plant pathogens, but genes involved in QDR are largely unknown. To identify genetic components and accelerate improvement of QDR in legumes to the root pathogen Aphanomyces euteiches, we took advantage of both the recently generated massive genomic data for Medicago truncatula and natural variation of this model legume. A high‐density (≈5.1 million single nucleotide polymorphisms (SNPs)) genome‐wide association study (GWAS) was performed with both in vitro and glasshouse phenotyping data collected for 179 lines. GWAS identified several candidate genes and pinpointed two independent major loci on the top of chromosome 3 that were detected in both phenotyping methods. Candidate SNPs in the most significant locus ( σ A 2  = 23%) were in the promoter and coding regions of an F‐box protein coding gene. Subsequent qRT‐PCR and bioinformatic analyses performed on 20 lines demonstrated that resistance is associated with mutations directly affecting the interaction domain of the F‐box protein rather than gene expression. These results refine the position of previously identified QTL to specific candidate genes, suggest potential molecular mechanisms, and identify new loci explaining QDR against A. euteiches .